The Effects of Operating Variables on Efficancy of Water Disinfection by Sodium Hypochlorite Using Al-Wathba Wastewater - Namoos, Bashaer Mahmoud; Abdul-Wahab, Majid I.; Abdul-Majeed, Wameath S. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The aim of this investigation was to study the impact of various reaction parameters on wastewater taken from Al-Wathba water treatment plant on Tigris River in south of Baghdad, Iraq with sodium hypochlorite solution. The parameters studied were sodium hypochlorite dose, contact time, initial fecal coliform bacteria concentration, temperature, and pH. In a batch reactor, different concentrations of sodium hypochlorite solution were used to disinfect 1L of water. The amount of hypochlorite ions in disinfected water was measured using an Iodimetry test for different reaction times, whereas the Most Probable Number (MPN) test was used to determine the concentration of coliform bacteria. Total Plate Count (TPC) was utilized in this study to count the number of colonies of common bacteria. Reaction variables that were examined showed that the increase in temperature, pH, and reaction time caused the concentration of Coliform bacteria to decrease, which in turn caused an accumulation-related increase in OCl- concentration. The optimum values of temperature and reaction pH were determined to be 8 and 29o C respectively. The kinetics of the reaction was examined in this study, and the results showed that Selleck model's order of reaction is two, with rate constants of 1.3791x10-5, 3.0806x10-5, and 5.738x10-5 L/(mole min) at 20o, 29o, and 37o C, respectively.